Perception and performance: an evaluation of multimodal feedback for the assessment of curve shape differences - Hollowood, Jacqueline (2011)
The EU-funded SATIN project sought to provide a multimodal interface to aid product designers in judging the quality of curved shapes. This thesis outlines a research programme designed to assist in the exploration of fundamental issues related to this project, and provide a means to evaluate the success of such interfaces more generally. Therefore, three studies were undertaken with the aim of exploring the value of haptic and sound feedback in the perception of curve shape differences, and through the knowledge gained provide an evaluative framework for the assessment of such interfaces.